Vote Buying dan Perilaku Pemilih Pemula: Kasus Pemilihan Gubernur Bali 2018 di Tabanan - Bayu Adhinata (Politika: Jurnal Ilmu Politik, 2019)
This article discusses vote-buying as a phenomenon in the 2018th Bali local head election process which affects the voting behavior of youth voters in Tabanan Regency. This research applies to qualitative methods. The research found that there is a linkage of giving money and gift as a form of aid to the society before and during the election can affect youth voter voting preferences. This article argues that the preference of youth voters influenced by their communities where they live and they herded to choose what community say so. Vote-buying in the form of ‘aid’ are liked by the community and youth voter seen it as something ordinary in the socio-political situation. With vote-buying strategy, the candidate can easily obtain a vote, especially from youth voter who has not yet decided their choice. In addition, vote-buying became a kind of magnet to attract youth voter sympathy.